2001
DOI: 10.1128/jvi.75.18.8837-8841.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Replication-Competent Feline Leukemia Virus, Subgroup A (FeLV-A), Tagged with Green Fluorescent Protein Reporter Exhibits In Vitro Biological Properties Similar to Those of the Parental FeLV-A

Abstract: We previously established that lymphoid tumors could be induced in cats by intradermal injection of ecotropic feline leukemia virus (FeLV), subgroup A, plasmid DNA. In preparation for in vivo experiments to study the cell-to-cell pathway for the spread of the virus from the site of inoculation, the green fluorescent protein (GFP) transgene fused to an internal ribosome entry site (IRES) was inserted after the last nucleotide of the env gene in the ecotropic FeLV-A Rickard (FRA) provirus. The engineered plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This allows for translation of the transgene from mRNAs that also direct synthesis of viral proteins. Such vectors have been developed mainly on basis of gammaretroviruses such as murine leukemia viruses (MLVs) (Jespersen et al, 1999;Logg et al, 2001a;Bachrach et al, 2002Bachrach et al, , 2003Pedersen and Duch, 2002;Solly et al, 2003) and feline leukemia virus (Chang et al, 2001). Retroviral genomes have a compact organisation with overlapping coding regions and densely packed regulatory ciselements.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for translation of the transgene from mRNAs that also direct synthesis of viral proteins. Such vectors have been developed mainly on basis of gammaretroviruses such as murine leukemia viruses (MLVs) (Jespersen et al, 1999;Logg et al, 2001a;Bachrach et al, 2002Bachrach et al, , 2003Pedersen and Duch, 2002;Solly et al, 2003) and feline leukemia virus (Chang et al, 2001). Retroviral genomes have a compact organisation with overlapping coding regions and densely packed regulatory ciselements.…”
Section: Introductionmentioning
confidence: 99%
“…EGFP is also commonly used in studies involving retroviral transfections (Persons et al 1998;Barrette et al 2000;Ramezani et al 2000;Tahara-Hanaoka et al 2002), in which the gene of interest and EGFP are simultaneously expressed as a bicistronic mRNA (Persons et al 1998;Barrette et al 2000;Ramezani et al 2000;Tahara-Hanaoka et al 2002). The inclusion of an internal ribosome entry site (IRES) element between the gene of interest and EGFP facilitates EGFP expression (Levenson et al 1998;Metz et al 1998;Jespersen et al 1999;Chang et al 2001;Abad et al 2002). Transgenic mice that express EGFP under the control of ubiquitous promoters (Okabe et al 1997) or cell-type specific promoters (Chiocchetti et al 1997;Kawakami et al 1999) are also popular, as are gene-targeted "knock-in" mice, which express EGFP under the control of an endogenous promoter (Mohrs et al 2001).…”
mentioning
confidence: 99%
“…Thus, using this stable construct design, RCR vectors can efficiently transduce and stably propagate over multiple infection cycles in a variety of cell lines in culture and tumors in vivo [Logg et al, 2001b, Logg et al, 2001a, Chang et al, 2001, Wang et al, 2003, Solly et al, 2003, including malignant human and rodent glioma cell lines [Wang et al, 2003, Solly et al, 2003, thereby achieving a tremendous in situ amplification effect after initial administration of a small inoculum in vitro. As predicted from their robust replicative capabilities, in independently confirmed studies, we [Wang et al, 2003, Solly et al, 2003 have found that intratumoral injection with as little as 10e4 total infectious units of RCR vector could spread and transmit an inserted transgene throughout entire subcutaneous and intracranial tumor masses in vivo, and achieved better therapeutic results than those requiring 1000-fold higher levels of replication-defective adenovirus [Solly et al, 2003], and those reported using 10,000-fold higher levels of highly concentrated replication-defective retrovirus vector supernatant [Tamura et al, 2001].…”
Section: Efficient Replication and Gene Transfer To Cancer Cellsmentioning
confidence: 97%